Prarancangan Pabrik Etilen Glikol Dari Etilen Oksida Menggunakan Proses Dow METEOR Dengan Disain Alat Utama Evaporator Ev-101 - Lestari Lestari; Sunarno Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Ethylene glycol is a colorless, odorless hygroscopic liquid with low volatility and viscosity. Ethylene glycol is used as an antifreeze in motor vehicle fluids, polyester fibers for clothing, filmmaking agents, cooling agents and heat exchangers, water-based formulas, and unsaturated polyesters. The purpose of establishing this ethylene glycol factory is to support efforts to save foreign exchange through import substitution of ethylene glycol, and increase employment, as well as assisting in ethylene glycol industry suppliers. Ethylene glycol factory with a capacity of 200,000 tons/year in Batam, Riau Islands. The ethylene glycol production process is carried out through Dow METEOR which consists of 4 stages, namely the preparation of raw materials, the formation of ethylene glycol, the concentration of ethylene glycol, and the stage of product separation. The main device design is evaporator 1 (EV-101), which is used to concentrate the crude glycol output from the reactor (R-101). Based on the economic analysis of the factory, the ethylene glycol plant is feasible to be established with a Payback Period (PBB) of 2 years, IRR 22.738%, Percent Return on Investment (ROI) of 30.59%, and Break Event Point (BEP) of 60%. Keywords: Dow METEOR, Ethylene glycol, Evaporator